Design and validation of two tools to observe and analyze history lessons in secondary education - Miralles-Sánchez, Pedro; Gómez-Carrasco, Cosme J.; Rodríguez-Medina, Jairo (Frontiers in Education, 2023)
This article focuses on the validation of two data collection instruments, one is the History Class Observation Tool (HCOT) and the other is focus groups with students, trainee teachers and tutors from secondary school classrooms. The main objective of the study is to obtain evidence of validity of the two instruments to be used in research on the design, validation, implementation, and evaluation of training units. All this in order to improve the teaching-learning process of historical thinking skills in high school students with the aim of forming critical citizens. The research approach is mixed explanatory, with a quasi-experimental design and a control group, using quantitative and qualitative methods for data collection and analysis. The article is composed of a theoretical framework where similar works on observation instruments are presented, followed by a description of the objective, research method and instruments, and the results of the validation. Finally, a discussion and conclusions of the results obtained, which have been favourable, are presented.